Stockholder Distribution Decisions: Share Repurchases or Dividends? - Woods, Donald H.; Brigham, Eugene F. (Journal of Financial and Quantitative Analysis, 1966)
Donald H. Woods, Eugene F. Brigham, Stockholder Distribution Decisions: Share Repurchases or Dividends?, The Journal of Financial and Quantitative Analysis, Vol. 1, No. 1, Proceedings of the First Annual Meeting of the Western Finance Association (Mar., 1966), pp. 15-26